Eye Blink Rates and Eyelid Twitches as a Non-Invasive Measure of Stress in the Domestic Horse - Katrina Merkies; Chloe Ready; Leanne Farkas; Abigail Hodder (Animals, 2019)
Physiological changes provide indices of stress responses, however, behavioural measures may be easier to determine. Spontaneous eye blink rate has potential as a non-invasive indicator of stress. Eyelid movements, along with heart rate (HR) and behaviour, from 33 horses were evaluated over four treatments: (1) control—horse in its normal paddock environment; (2) feed restriction—feed was withheld at regular feeding time; (3) separation—horse was removed from visual contact with their paddock mates; and (4) startle test—a ball was suddenly thrown on the ground in front of the horse. HR data was collected every five s throughout each three min test. Eyelid movements and behaviours were retrospectively determined from video recordings. A generalized linear mixed model (GLIMMIX) procedure with Sidak’s multiple comparisons of least squares means demonstrated that both full blinks (16 ± 12b vs. 15 ± 15b vs. 13 ± 11b vs. 26 ± 20a full blinks/3 min ± SEM; a,b differ p < 0.006) and half blinks (34 ± 15ab vs. 27 ± 14bc vs. 25 ± 13c vs. 42 ± 22a half blinks/3 min ± SEM; a,b,c differ p < 0.0001) decreased during feed restriction, separation and the startle test compared to the control, respectively. Eyelid twitches occurred more frequently in feed restriction (p < 0.0001) along with an increased HR (p < 0.0001). This study demonstrates that spontaneous blink rate decreases while eyelid twitches increase when the horse experiences a stressful situation.